Molecularly Distinct Clathrin-Coated Pits Differentially Impact EGFR Fate and Signaling - Pascolutti, Roberta; Algisi, Veronica; Conte, Alexia; Raimondi, Andrea; Pasham, Mithun; Upadhyayula, Srigokul; Gaudin, Raphael; Maritzen, Tanja; Barbieri, Elisa; Caldieri, Giusi; Tordonato, Chiara; Confalonieri, Stefano; et al. (Cell reports (Cambridge), 2019)
Adaptor protein 2 (AP2) is a major constituent of clathrin-coated pits (CCPs). Whether it is essential for all forms of clathrin-mediated endocytosis (CME) in mammalian cells is an open issue. Here, we demonstrate, by live TIRF microscopy, the existence of a subclass of relatively short-lived CCPs lacking AP2 under physiological, unperturbed conditions. This subclass is retained in AP2-knockout cells and is able to support the internalization of epidermal growth factor receptor (EGFR) but not of transferrin receptor (TfR). The AP2-independent internalization mechanism relies on the endocytic adaptors eps15, eps15L1, and epsin1. The absence of AP2 impairs the recycling of the EGFR to the cell surface, thereby augmenting its degradation. Accordingly, under conditions of AP2 ablation, we detected dampening of EGFR-dependent AKT signaling and cell migration, arguing that distinct classes of CCPs could provide specialized functions in regulating EGFR recycling and signaling.